Similitude laws for the sound radiation of flat orthotropic flexural panels. (22nd December 2020) - Berry, Alain; Robin, Olivier; Franco, Francesco; Rosa, Sergio De; Petrone, Giuseppe
Abstract: Similitude laws in vibro-acoustics are potentially interesting to extrapolate measurements performed on small structures to the response of larger structures. This paper examines similitude laws for the vibroacoustic response of flat orthotropic flexural rectangular panels radiating sound in a semi-infinite light fluid medium. The scaling parameters considered are the panel size and thickness, its material properties (mass density, elastic moduli) and the properties of the acoustic medium (mass density, sound speed). It is shown that, while no general similarity laws exist for the near-field acoustic radiation, such laws exist for the case of far-field acoustic radiation. Acoustic directivity measurements performed on various isotropic panels confirm the vibroacoustic scaling laws derived theoretically.